2021
DOI: 10.1186/s13023-021-01881-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genotype–phenotype correlation with MORC2 mutated Axonal Charcot–Marie–Tooth disease in a cohort of Chinese patients

Abstract: Background Charcot–Marie–Tooth (CMT) disease is an exciting field of study, with a growing number of causal genes and an expanding phenotypic spectrum. The microrchidia family CW-type zinc finger 2 gene (MORC2) was newly identified as a causative gene of CMT2Z in 2016. We aimed to describe the phenotypic-genetic spectrum of MORC2-related diseases in the Chinese population. Methods With the use of Sanger sequencing and Next Generation Sequencing (NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other side, the early onset SMA-like/DIGFAN syndrome characterized by central and peripheral nervous systems damage, and developmental anomalies. (Semplicini et al, 2017), p.Q400R (Ando et al, 2017), p.D466G (Duan et al, 2021;Sivera et al, 2021) were associated with a CMT2 scapuloperoneal phenotype, whereas p.R319C (Sivera et al, 2021), p.C407Y (Ando et al, 2017) were associated with a pure sensory-motor polyneuropathy without proximal involvement. This discrepancy in phenotype could be explained by a differential effect of the various mutations on MORC2 activity and/or by differences in the age of the patient at the time of examination.…”
Section: Cmt2zmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other side, the early onset SMA-like/DIGFAN syndrome characterized by central and peripheral nervous systems damage, and developmental anomalies. (Semplicini et al, 2017), p.Q400R (Ando et al, 2017), p.D466G (Duan et al, 2021;Sivera et al, 2021) were associated with a CMT2 scapuloperoneal phenotype, whereas p.R319C (Sivera et al, 2021), p.C407Y (Ando et al, 2017) were associated with a pure sensory-motor polyneuropathy without proximal involvement. This discrepancy in phenotype could be explained by a differential effect of the various mutations on MORC2 activity and/or by differences in the age of the patient at the time of examination.…”
Section: Cmt2zmentioning
confidence: 95%
“…direct sequencing in 52 unrelated probands, a de novo heterozygous missense mutation p.S87L was identified in a patient with infantile-onset SMA-like presentation associated with microcephaly, general weakness and areflexia (Sevilla et al, 2016). After this first report, clinicians re-examined sequencing data from patients with genetically unsolved neuropathies for mutations in MORC2 and identified a similar p.S87L mutation in two unrelated patients with infantile-onset SMA-like picture associated with generalized hypotonia, sensory loss, developmental delay, cataract, scoliosis, dysmorphic face (Hyun et al, 2016) or in one patient with scoliosis, cerebellar hypoplasia, and intellectual disability (Duan et al, 2021; Table 1). Besides the p.S87L mutation, patients with similar SMA-like picture were rapidly identified in two unrelated families with a de novo p.T424R (c.1271C > G) MORC2 mutation associated with cerebellar atrophy, diaphragmatic paralysis, developmental delay (Schottmann et al, 2016;Zanni et al, 2017).…”
Section: Cmt2zmentioning
confidence: 99%
“…In the past decade, progress in genome-wide association studies has identified several independent genetic loci of MORC2 for diseases. For instance, MORC2 mutations are associated with some disorders, 34 , 35 , 36 including Charcot-Marie-Tooth (CMT) disease, 37 , 38 , 39 , 40 , 41 spinal muscular atrophy, 24 , 42 , 43 and neurological disorders, 44 especially Charcot-Marie-Tooth disease type 2Z (CMT2Z), 38 , 45 thus allowing a better understanding of the genetic architecture of MORC2. Mounting evidence has shown that mutations in MORC2 may be strongly associated with the development of multiple cancers.…”
Section: Mutationmentioning
confidence: 99%